How Do Defaults Affect Behavior of Individual Retirement: Evidence from Ankara - Fahriye Öztürk; Havva Serim (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Turkey is one of the few countries that has introduced national-level automatic enrollment in private pension systems to encourage people to save for retirement. Although the policy's effectiveness is debatable, it is fair to conclude that it has accelerated enrolment in individual pension plans. This is due to the fact that defaults have a significant impact on saving behavior. However, there are few empirical data that explain how defaults operate. To find out, we created a survey for Ankara public employees in order to explore possible demographic, financial, and behavioral constructs for automatic enrollment choices. Gender, marital status, and the number of dependents in the family all have an impact on the decisions. Other noteworthy findings concern behavioral constructs: Ankara public employees who find individual pension systems complex are more likely to opt out, and the public authority endorsement effect greatly reduces the risk of quitting the system. These findings show that there is a need for more educational and informational efforts on the pension system, and that policymakers have a significant amount of responsibility as a result of this strategy.